Metropolitan cities under transition: the example of Hamburg/Germany - Amelie Boje; Ingrid Ott; Silvia Stiller (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2010)
In the intermediate and long run energy prices and hence transportation costs are expected to increase significantly. According to the reasoning of the New Economic Geography this will strengthen the spreading forces and thus affect the economic landscape. Other influencing factors on the regional distribution of economic activity include the general trends of demographic and structural change. In industrialized countries, the former induces an overall reduction of population and labor force whereas the latter implies an ongoing shift to the tertiary sector and increased specialization. Basically, cities provide better conditions to cope with these challenges than rural regions. Since the general trends affect all economic spaces similarly, city-specific factors also have to be considered in order to derive the impact of rising energy costs on future urban development. With respect to Hamburg regional peculiarities include the overall importance of the harbor as well as the existing composition of the industry and the service sector. The analysis highlights that rising energy and transportation costs will open up a range of opportunities for the metropolitan region.
Keywords: R11; J11; 330; Urban development; regional specialization; structural change; demographic change; transportation costs